Visual and Automatic Evaluation of Vocal Fold Mucosal Waves Through Sharpness of Lateral Peaks in High-Speed Videokymographic Images - Kumar, S Pravin; Phadke, Ketaki Vasant; Vydrová, Jitka; Novozámský, Adam; Zita, Aleš; Zitová, Barbara; Švec, Jan G (Journal of voice, 2020)
INTRODUCTION: The sharpness of lateral peaks is a visually helpful clinical feature in high-speed videokymographic (VKG) images indicating vertical phase differences and mucosal waves on the vibrating vocal folds and giving insights into the health and pliability of vocal fold mucosa. This study aims at investigating parameters that can be helpful in objectively quantifying the lateral peak sharpness from the VKG images. METHOD: Forty-five clinical VKG images with different degrees of sharpness of lateral peaks were independently evaluated visually by three raters. The ratings were compared to parameters obtained by automatic image analysis of the vocal fold contours: Open Time Percentage Quotients (OTQ) and Plateau Quotients (PQ). The OTQ parameters were derived as fractions of the period during which the vocal fold displacement exceeds a predetermined percentage of the vibratory amplitude. The PQ parameters were derived similarly but as a fraction of the open phase instead of a period. RESULTS: The best correspondence between the visual ratings and the automatically derived quotients were found for the OTQ and PQ parameters derived at 95% and 80% of the amplitude, named OTQ95, PQ95, OTQ80 and PQ80. Their Spearman's rank correlation coefficients were in the range of 0.73 to 0.77 (P < 0.001) indicating strong relationships with the visual ratings. The strengths of these correlations were similar to those found from inter-rater comparisons of visual evaluations of peak sharpness. CONCLUSION: The Open time percentage and Plateau quotients at 95% and 80% of the amplitude stood out as the possible candidates for capturing the sharpness of the lateral peaks with their reliability comparable to that of visual ratings.
Keywords: biomechanika; zraková percepce; Image Interpretation, Computer-Assisted; lidé; Visual Perception; Voice Quality; mínění; hlasové řasy; Phonation; laryngoskopie; sliznice hrtanu; vibrace; Video Recording; Judgment; fonace; retrospektivní studie; Humans; Vibration; Predictive Value of Tests; poruchy hlasu; Voice Disorders; kymografie; audiovizuální záznam; Kymography; automatizace; Vocal Cords; Biomechanical Phenomena; Laryngoscopy; Time Factors; interpretace obrazu počítačem; Automation; časové faktory; Laryngeal Mucosa; Retrospective Studies; kvalita hlasu; prediktivní hodnota testů